Perancangan UI/UX Fitur Pariwisata pada Aplikasi Garut Hebat Super App Menggunakan Metode Prototipe - Futri Gina Firnanda; Bayu Pamungkas (Bulletin of Computer Science Research, 2026)
The tourism feature on the Garut Hebat Super App currently has limitations in navigation structure, presentation of destination information, and a lack of interactive elements, making it difficult for users to obtain tourism information quickly and in a structured manner. This study aims to design the UI/UX of the tourism feature using the Prototype method to produce an interface design that is easier to use and suits user needs. The Prototype method is implemented through the stages of communication, quick plan, modeling quick design, construction of prototype, and delivery and feedback carried out iteratively based on user feedback. The results of the study are interactive prototypes (high-fidelity) that include destination video features, ticket price information, and integrated tourist route maps. Usability evaluation was conducted using the System Usability Scale method on 50 respondents Test results show an average score of 80.09, placing it in the "acceptable" category, with a good level of usability that is acceptable to users. This value indicates that the prototype has a fairly good level of usability and is acceptable to users, although there are still several interface aspects that need to be improved. This research contributes to the design of a prototype-based UI/UX for tourism features on an integrated public service platform (super app) that combines destination information, ticket prices, travel videos, and route navigation in a single interface. The research findings are expected to serve as a reference for developers of regional public service applications in improving the quality of digital tourism services that are oriented towards user needs.